One-Pot, Sequential Four-Component Synthesis of Thiazepine Derivatives - Alizadeh, Abdolali; Feizabadi, Masoomeh; Bayat, Fahimeh; Zhu, Long-Guan (Synlett, 2014)
A one-pot, sequential, four-component procedure for the synthesis of thiazepines by the reaction of primary amines, 1,3-dicarbonyl compounds, aryl isothiocyanates, and chloroacetyl chloride at room temperature is described. Advantages of this protocol include ease of handling, regioselectivity, the absence of a metal catalyst, and moderate yields.
Keywords: thiazepines; heterocycles; multicomponent reactions; amines; dicarbonyl compounds